A reflection of grace: the place of humor in the theology of Flannery O'Connor - John N. Sommerville Jr (Ilha do Desterro)
Carter Martin has written that the "most troublesome critical problem" for those who read the stories of Flannery O'Connor is the "justification of the laughter which her work most assuredly does arouse"(5). This dilemma involves, among other things, the question of where humor fits in the world of "mystery", in the eternal and Christian context where, O'Connor emphasizes, her stories inevitably occur. Such a question is not easy to answer.